Simultaneous large continuous band gap tunability and photoluminescence enhancement in GaSe nanosheets via elastic strain engineering. (February 2017) - Wu, Yecun; Fuh, Huei-Ru; Zhang, Duan; Coileáin, Cormac Ó; Xu, Hongjun; Cho, Jiung; Choi, Miri; Chun, Byong Sun; Jiang, Xuju; Abid, Mourad; Abid, Mohamed; Liu, Huajun; et al.
Abstract: For applications in wearable human-device interfaces and optoelectronics, flexible materials capable of supporting spatial and uninterrupted bandgap tunability are of immense value. We demonstrate theoretically and experimentally the wide bandgap tunability of GaSe nanosheets, with simultaneous PL enhancement, via elastic strain engineering at room temperature. The elastic strain gives rise to a continuously variable electronic band structure profile, with a rate of 40 meV/1%, and a 3-fold enhancement in PL intensity is achieved when a uniaxial strain of 1% is introduced. An additional effect is that a new exciton state arises when the strain is raised beyond 0.6%. This work suggests that strain engineering can effectively modulate/control the generation, separation, transport, and recombination of photo-induced charge carriers in GaSe, making it a valuable material for flexible optoelectronic-mechanical applications. Graphical abstract: Highlights: Wide bandgap tunability of GaSe nanosheets, with simultaneous PL enhancement, via elastic strain engineering at room temperature. A linear tuning rate of optical band gap of 40 meV/% for uniaxial strain has been achieved, comparable to monolayer MoS2. Threefold enhancement in PL intensity achieved with a uniaxial strain of 1%. Strain engineering used to control generation, separation, transport, and recombination of photo-induced charge carriers in GaSe. New exciton state demonstrated when strain is greater than 0.6%, which shifts in the direction opposite to the main exciton state. Suggests route to more efficient capture of optical spectrum, and exciton concentration and trapping by mechanical deformation.